Analysis of the implementation of environmental accounting in Village-Owned enterprises (BUMDES) to realize green accounting in Durjela village, pulau-pulau Aru district - Fanny Monica Anakotta; Yustinus Lambyombar (SEAN Institute, 2024)
Durjela village has experienced a decline in the number of tourists because many places supporting village facilities and infrastructure have been damaged. Lack of attention from Village-Owned Enterprises to environmental problems such as damaged embankments, no repairs to damaged facilities and infrastructure in the tourism sector. The purpose of this study is to: analyse the Application of Environmental Accounting to Village-Owned Enterprises to Realise Green Accounting in Durjela Village. This research is qualitative research. Data analysis and data analysis techniques through steps such as Data Collection, Data Reduction, Data Presentation and Conclusion Drawing, The result of this study is that Bumdes has not implemented environmental accounting to realise green accounting in accordance with procedures.